ANALISIS PROBABILITAS PEMILIHAN MODA PUBLIC BOAT DAN FAST BOAT RUTE PENYEBERANGAN BANGSAL – GILI INDAH - ROHANI ROHANI; HASYIM HASYIM (GANEC SWARA, 2024)
The most popular modes of transportation on the crossing from Bangsal Harbor to Gili Indah are public boats and fast boats. The respective advantages and disadvantages of these two modes are that fast boats excel in fast travel times, while public boats excel in cheaper travel costs. The aim of this research is to obtain factors that influence passengers' decisions in choosing a mode, to find out user characteristics and to obtain the probability that passengers choose public boats and fast boats.Data was obtained from the results of a questionnaire using the stated preference method which offers 7 change scenarios and related choices such as cost (X1), travel time (X2), and waiting time (X3) regarding the choice of public boat and fast boat modes (Y). The results of the choices of public boat and fast boat users will be known through the proportion of public interest in each scenario. Factors that influence mode choice can be identified using multiple linear regression analysis. Then a binary logit analysis of the difference is carried out to obtain the probability of mode choice. The research results show that the utility function equation is Y = -0.3864 – 0.04299X1 – 0.06177X2 – 0.02577X3. Factors that influence passengers' decisions in choosing public and fast boats are cost (X1), travel time (X2), and waiting time (X3). Using the binary logit difference method, the probability of choosing the mode for the Bangsal-Gili Indah crossing route is public boat 79% and fast boat 21%.